2019
DOI: 10.1097/bot.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

Knee Disarticulations Versus Transfemoral Amputations: Functional Outcomes

Abstract: Objectives: To determine whether there is a patient-reported functional difference between combat-related knee disarticulations (KDs) and transfemoral amputations (TFAs). Setting: Role 3 Military Trauma Centers. Patients: We identified and contacted all KDs and TFAs performed at the Walter Reed National Military Medical Center, Walter Reed Army Medical Center, and National Naval Medical Center from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…However, the Mazet and Gritti-Stokes surgical techniques claim to reduce volume of the residual limb by shortening the femur and reducing the bulge of the condyles by shaving or removing them completely, although the bulbous condyles can provide a better prosthetic suspension. 15 Few outcome data relating to TKA are reported and coupled with the absence of a standardised surgical technique; comparison of TKA to AKA is not possible. The variations in TKA surgical technique (classical, Mazet or Gritti-stokes, with their own respective modifications) compound this challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the Mazet and Gritti-Stokes surgical techniques claim to reduce volume of the residual limb by shortening the femur and reducing the bulge of the condyles by shaving or removing them completely, although the bulbous condyles can provide a better prosthetic suspension. 15 Few outcome data relating to TKA are reported and coupled with the absence of a standardised surgical technique; comparison of TKA to AKA is not possible. The variations in TKA surgical technique (classical, Mazet or Gritti-stokes, with their own respective modifications) compound this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Classical approach. In the classical approach [Figure 1(a)], the femur is left intact, 4,[11][12][13][14][15][16][17][18][19][20] except for the technical modification described by Vaucher and Blanc 21 where the femoral condylar cartilage and corners are excised to reduce the size of the condyles. The menisci are removed, except by Baumgartner (1979) who reported that the menisci could 'add cover' to the weight bearing femoral condyles in non-vascular patients.…”
Section: Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, the AAOS Hip and Knee Questionnaire has not been used in any major clinical trials. It has been used to assess outcomes in patients with slipped capital femoral epiphysis , and the AAOS Lower Limb Questionnaire appears in numerous studies covering a broad range of musculoskeletal topics, including outcomes of limb lengthening and lower ‐ extremity amputation .…”
Section: American Academy Of Orthopaedic Surgeons Hip and Knee Questimentioning
confidence: 99%